Vera lux illa est quae illuminat: the Christian humanism of Augustine - Bonner, Gerald (Studies in church history, 1977)
In 427, three years before his death, Augustine of Hippo compiled the Retractations, a kind of critical bibliography in which he passed in chronological review his writings as a catholic Christian, clarifying, defending and, where necessary, correcting passages which the course of events or his own theological development had called in question. In a very human way Augustine tended, in practice, to defend his previously-expressed views to a rather greater degree and to criticise them less than had been his original intention; but this means that where he declares a change of opinion, this statement may fairly be regarded as his final and definitive view. Two such statements are relevant to our purposes here: in his review of his earliest Christian work, Against the Academics, which appeared in 386, Augustine expresses his displeasure at the praise he there bestowed on the Platonist and Academic philosophers; while in his discussion of the two books On Order, which were written at the end of the same year, he regrets that he attributed too much to those liberal studies, of which many of the saints had been ignorant and many of their most enthusiastic disciples lacking in sanctity. Such views would seem, on first reading, to be exactly what we should expect of Augustine in the last years of his life, the result of an increased rigorism brought about by many years of controversy, which had left little of the humanism which had marked his first years as a Christian.